THE RELATIONSHIP BETWEEN KNOWLEDGE OF THE USE OF PERSONAL PROTECTIVE EQUIPMENT AND THE SELF EFFICACY OF PUSKESMAS NURSES AGAINST COVID-19 MANAGEMENT - Valen Fridolin Simak; Kristamuliana Kristamuliana (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
The COVID 19 pandemic is a case which continues to be felt by the community especially health workers. Data shows an increase in cases of health workers, especially nurses as the frontliner, this is due to one of them the use of protective equipment. The purpose of this study was to analyze the relationship between the knowledge of the use of personal protective equipment with the Puskesmas Nurses self-efficacy on the management of COVID 19. The method used in this study was analytic descriptive with a cross-sectional approach and used 146 samples surveyed online for 1 month based on inclusion and exclusion criteria. The variable knowledge of the use of personal protective equipment was measured using a questionnaire developed by researchers based on the personal protective equipment guidelines by the Covid Task Force 19, (2020); Ministry of Health, (2020), while the variable of self-efficacy uses the General Self-efficacy Scale questionnaire by Schwarzer and Jerusalem (2010). The results showed a significant relationship between the knowledge of the use of personal protective equipment with the efficacy of the Puskesmas Nurse on the management of COVID 19 p-value 0.016. OR 2,780 which means nurses who have knowledge using good personal protective equipment have an opportunity of 2,780 times to have a good self-efficacy (sure) to the management of COVID 19 compared to nurses who have less knowledge. Based on the results of this study, it is necessary to develop human resources including nurses conducted by the government as policy makers. Through this research, the researcher proposes that further researchers can develop this research by linking other factors that can influence nurse self-efficacy.